Drifting, mending - Leonard, Zach, author; Lehene, Marius, advisor; Ryan, Ajean, committee member; Tornatzky, Cyane, committee member; Cohen, Adrienne, committee member (Colorado State University. Libraries, 2021)
I see my everyday life and my art practice as connected by the activity of walking. My art practice attempts to express poetic qualities of discarded (broken) objects found in my everyday life and in my walking (drifting). Overall, this practice is guided by a sharpened sensibility towards everything that is broken or bereft, including bereft-of-a-world. I gained this shift in sensibility after a car accident, in my teens. My propensity for walking made it a preferred means to act on my sensibility for everything that is broken or bereft (from simple actions, ideas, and objects), enabling me to engage with concepts of space and place. The combination of Michel de Certeau and Henri Lefebvre's ontology and epistemology of space and place influenced my creative process. In addition, the Situationist practice of detournement – a method of appropriating and altering something (an event, or – as often in my case – objects) to create new meaning – is possibly as important as walking in my art practice. Walking is a method of research and detournement is an expressive action of that method. In the studio I, in a sense, began mending, bringing them back into a world. With the small artistic gestures or simply articulating them into a space (on a wall, a floor) or into a combination with another. I strive for a sense of poetry in humble materials, creating works that exist in the present moment, reflecting the fragility of the world, and allowing for individual moments of viewer creativity, experiences, and perceptions.
Keywords: broken; practice; walking; mending; art; space